PERAN ORANG TUA DALAM MENGATASI KECANDUAN GADGET PADA ANAK SD DI KELURAHAN GERUNUNG, LOMBOK TENGAH - Fathina Soleha; Syafruddin; Nursaptini (STKIP Subang, 2026)
This study aims to understand, identify, and analyze the role of parents in overcoming gadget addiction and the impact of gadget addiction on elementary school children in Gerunung Village, Central Lombok. This research uses a qualitative approach with a case study method. The types of data used are primary and secondary data. The subjects in this study are parents who are directly involved and play a role in addressing children’s gadget addiction, while the informants in this research are the village head of Tanggak, neighbors, and classroom teachers. The data collection methods applied include observation, interviews, and documentation. The data analysis process in this study was carried out in three stages: (1) data reduction, (2) data presentation, and (3) conclusion drawing. Meanwhile, the validity of the data was tested using data triangulation techniques, including (1) source triangulation, (2) technique triangulation, and (3) time triangulation.The results of this study show that there are three strategic roles carried out by parents to overcome children’s gadget addiction: (1) the role of facilitator, (2) the role of mediator, and (3) the role of motivator.